Pemanfaatan Sampah Plastik Menjadi Bantal Kursi Untuk Mengurangi Pencemaran Lingkungan - Tengku Abdillah Azis; Dini Afrilia; Nurul Ilmi; Maria Joito Gulton; Melinda Suriani Harefa (Jurnal Bintang Pendidikan Indonesia, 2024)
This research aims to address the environmental pollution issue caused by plastic waste in Bantan Timur Village, Medan Tembung Subdistrict, by transforming plastic waste into a valuable product, namely seat cushions. The problem of waste has become a global challenge, especially with the increasing population and activities. The rise in waste leads to negative impacts on the environment, such as disease outbreaks, floods, and a decline in aesthetic value. In this context, this article proposes a solution through the Research and Development (R&D) research method to produce seat cushions from plastic waste. Plastic waste is processed through steps of washing, drying, cutting, and packaging. The product is expected to raise awareness about proper waste management, reduce environmental pollution, and have a positive economic impact. Making seat cushions from plastic waste serves as a practical example of sustainable waste management, involving ecological and social aspects. The results are anticipated to inspire similar efforts in other regions, creating creative and sustainable solutions to address environmental pollution issues.